1715PSoft tissue sarcomas express a distinct mRNA immune profile. (1st October 2019) - Grünwald, V; Laenger, F; Kunitz, A; Schuler, M; Schoeffski, P; Kopp, H-G; Bauer, S; Kasper, B; Lindner, L; Chemnitz, J M; Crysandt, M; Stein, A; et al.
Abstract: Background: There is a need for novel therapies in metastatic STS, rendering checkpoint inhibitors (CPI) of interest in STS. Immune cell infiltrates are thought as a prerequisite for CPI efficacy and its role remains vague in STS. We analyzed whether the immune profile differed for STS treated within the phase II EPAZ study (NCT01861951). Methods: RNA samples were measured using the PanCancer Immune Profiling Panel from the nCounter® Analysis System. FCF1, HDAC3, ZKSCAN5, MRPS5 and EIF2B4 were used as housekeeping genes. Samples were categorized in three groups based on their overall mRNA expression via unsupervised random forest analysis. Differences in gene expression were tested by T-tests or ANOVA, with correction for multiple testing. Ingenuity Pathway Analysis (IPA) were performed for activity prediction. K-M plots were used for survival estimates and log-rank analyses for comparisons. Results: Specimens were available in 70/120 patients and 31 were assessable by immune profiling. 12 pts. received doxorubicin (DOX) and 18 pazopanib (PAZ). Median progression free survival (PFS) and median overall survival (OS) for the total cohort were 2.6 mo. and 11.6 mo., respectively. Patients were clustered in high (n = 4)/mixed (n = 20)/low (n = 7) mRNA profile expressions. While OS varied numerically between clusters (11.1/9.0/28.9 mo.), values were not significant (P = 0.5573). A similar pattern was detected for PFS (4.2/1.5/8.9 mo.; P = 0.4127). Conclusions: Our study indicates that STS express a differential mRNA immune profile. However, clusters were not associated with outcome measures. A major limitation is the small sample size. Clinical trial identification: NCT01861951. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: V. Grünwald: Honoraria (self), Research grant / Funding (institution): Novartis; Honoraria (self), Advisory / Consultancy: Lilly; Honoraria (self): PharmaMar. M. Schuler: Research grant / Funding (institution): Novartis. P. Schoeffski: Honoraria (institution), Advisory / Consultancy: Daiichi; Honoraria (institution), Advisory / Consultancy: Eisai; Honoraria (institution), Advisory / Consultancy: Lilly; Honoraria (institution), Advisory / Consultancy: Medpace; Honoraria (institution), Travel / Accommodation / Expenses: Novartis; Honoraria (institution): Biovitrium; Honoraria (institution): 6th element capital; Advisory / Consultancy, Travel / Accommodation / Expenses: Adaptimmune; Advisory / Consultancy: AstraZeneca; Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Bayer; Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Blueprint; Advisory / Consultancy, Travel / Accommodation / Expenses: BMS; Advisory / Consultancy, Travel / Accommodation / Expenses: BoBoehringer Ingelheim; Advisory / Consultancy, Travel / Accommodation / Expenses: Cristal Therapeutics; Advisory / Consultancy, Travel / Accommodation / Expenses: Epizyme; Advisory / Consultancy, Travel / Accommodation / Expenses: Genzyme; Advisory / Consultancy, Travel / Accommodation / Expenses: Ipsen; Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Loxo Oncology; Advisory / Consultancy, Travel / Accommodation / Expenses: Nektar; Advisory / Consultancy, Travel / Accommodation / Expenses: Novartis. H. Kopp: Advisory / Consultancy, Travel / Accommodation / Expenses: MSD; Advisory / Consultancy, Travel / Accommodation / Expenses: BMS; Advisory / Consultancy, Travel / Accommodation / Expenses: Sanofi; Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Novartis; Speaker Bureau / Expert testimony: LeoPharma; Speaker Bureau / Expert testimony: Pfizer; Travel / Accommodation / Expenses: Lilly; Travel / Accommodation / Expenses: Amgen. B. Kasper: Honoraria (self), Advisory / Consultancy: Bayer; Honoraria (self), Advisory / Consultancy: Lilly; Honoraria (self), Advisory / Consultancy: Novartis; Advisory / Consultancy: Eisai ; Honoraria (self), Research grant / Funding (institution): PharmaMar. L. Lindner: Advisory / Consultancy: Novartis; Honoraria (self): Lilly; Honoraria (self): Eisai; Honoraria (self): EZ Medconsultant; Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: PharmaMar; Research grant / Funding (institution): Sennewald. J.M. Chemnitz: Honoraria (self): Ablynx; Advisory / Consultancy: Amgen; Advisory / Consultancy: Ablynx; Travel / Accommodation / Expenses: Amgen; Travel / Accommodation / Expenses: PharmaMar. G. Egerer: Honoraria (self): MSD; Advisory / Consultancy: MSD; Honoraria (self): PharmaMar; Travel / Accommodation / Expenses: MSD; Travel / Accommodation / Expenses: Astellas. All other authors have declared no conflicts of interest.